Reakce na bombardování SR Jugoslávie v roce 1999 v české politické debatě - Ivaniushin, Mikhail (Univerzita Karlova, Filozofická fakulta, 2020)
The aim of the thesis is to map and analyze the Czech public debate about the bombing of the Federal Republic of Yugoslavia by NATO air forces in 1999. The North Atlantic Alliance attack on the FRY, which followed shortly after the Czech Republic had joined the Organization. Part of the political representation reacted to NATO's actions with restraint or regret, while the current, represented mainly by President Havel, became a principled supporter of the attack, even on the international political scene. The work deals with various levels of this debate: the initiation of individual actors in the problems of the NATO Operation in Yugoslavia, the starting points, argumentation strategies or links with other topics. It tries to reveal secondary motivations in the formulation of individual opinions (considerations of the security interests of the Czech Republic, worldview, prejudices, etc.). The source base of the work is mainly periodicals, especially the most read dailies. Klíčová slova (anglicky): Czech Republic, Serbia, Federal Republic of Yugoslavia, Yugoslavian crisis, The conflict in the Balkans in 1999, NATO Air Strikes Against Yugoslavia in 1999, NATO Cílem diplomové práce je zmapovat a analyzovat českou veřejnou debatu o bombardování Svazové republiky Jugoslávie leteckými silami NATO v roce 1999. Útok Severoatlantické aliance na SRJ, který následoval krátce po vstupu České republiky do aliance, rozdělil české veřejné mínění i politickou scénu v názoru na oprávněnost této intervence. Část politické reprezentace reagovala na akce NATO zdrženlivě či s politováním, zatímco proud reprezentovaný zejména prezidentem Havlem se stal principiálním zastáncem útoku, a to i na mezinárodní politické scéně. Práce se bude zabývat různými rovinami této debaty: zasvěceností jednotlivých aktérů do problémů operace NATO v Jugoslávii, názorovými východisky, strategiemi argumentace či propojením s jinými tématy. Pokouší se odhalit vedlejší motivace při formulování jednotlivých názorů (ohledy na bezpečnostní zájmy České ...